Design And Implementation Of Temperature Measuring Device Using Max6675 And Thermocouple On Wet Cooling Tower - Umurani, Khairul; ., Rahmatullah; Nasution, Arya Rudi; Zufri, M Sayid (Fakultas Teknik UMSU, 2024)
Cooling Tower or cooling tower is a technology used in the industrial world, cooling tower works to cool water fluid by using wind power that comes from a fan or blower, how the cooling tower works is basically hot water coming from the machine is flowed to the cooling tower then water through the fill-fills that are in the cooling tower and in direct contact with the air, the cooling tower is focused on reducing the temperature of the inlet water until it leaves it, while the water temperature reading uses a thermocouple sensor. A thermocouple is a temperature sensor capable of reading temperatures from -200 ℃ to 1200 ℃. This cooling tower uses arduino mega circuit, PCB board, MAX6675 module and thermocouple. How to read the temperature on the cooling tower using a computer or laptop with Microsoft Excel that is already connected to the PLX-DAQ software. The data that has been obtained is then tested using SPSS (Statiscal Product and Service Solutions) software, testing using 3 types, namely normal distribution, standard deviation, and reliability. The overall results of the thermocouple sensor on the Wet Cooling Tower show normal performance according to statistical testing, including normal distribution, standard deviation, and reliability. All data and values obtained have met the established standards